2011
DOI: 10.1016/j.jvs.2010.08.084
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic arterial injuries of spine and orthopedic operations

Abstract: Arterial injuries following orthopedic and spine operations can be successfully managed by both open and endovascular techniques. Significant morbidity and increased length of stay is common. Patient dissatisfaction with the complication and need for ensuing treatment can have significant medicolegal consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 13 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…6,7 Consistent with contemporary literature this study reports similar findings. 1,5,7 The one arterial injury we report was unrelated to the exposure; however, it is important to emphasize that the instrumentation has significant potential complications and it is strongly recommended that all surgeons remain close during the procedure and that a team approach is employed when retractors need re-adjustment to accommodate bulky instruments ( Figure 2). Venous injury is considered more likely to occur with secondary exposure due to adhesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6,7 Consistent with contemporary literature this study reports similar findings. 1,5,7 The one arterial injury we report was unrelated to the exposure; however, it is important to emphasize that the instrumentation has significant potential complications and it is strongly recommended that all surgeons remain close during the procedure and that a team approach is employed when retractors need re-adjustment to accommodate bulky instruments ( Figure 2). Venous injury is considered more likely to occur with secondary exposure due to adhesions.…”
Section: Discussionsupporting
confidence: 92%
“…Chiriano et al 6 reported a 3% rate of lifethreatening vascular injury and Hans et al 7 reported five of 560 (1%) patients with ARES developed significant arterial complications. 6,7 Consistent with contemporary literature this study reports similar findings. 1,5,7 The one arterial injury we report was unrelated to the exposure; however, it is important to emphasize that the instrumentation has significant potential complications and it is strongly recommended that all surgeons remain close during the procedure and that a team approach is employed when retractors need re-adjustment to accommodate bulky instruments ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The source for the neurological impairment can be central (motor neuron disease, parasagittal cortical or subcortical cerebral lesions) or peripheral (lumbar radiculopathy, mononeuropathies of the deep peroneal, common peroneal, or sciatic nerves) [1-3]. In addition, there have been several case reports of foot drop due to an unusual etiology such as Baker's cyst [4], Hodgkin's lymphoma [5], Perineurioma [6], Paget's disease [7] and iatrogenic foot drop after spinal anesthesia [8] or lumbar surgery [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic vascular injuries, due to the particular nature of such pathology, are associated with high morbidity and mortality in the postoperative period. 1,2 This dangerous and sometimes life-threatening complication is being increasingly reported in the literature. It results mainly from the large number of diagnostic and therapeutic interventions requiring vascular access, as well as complex and extensive surgical repair procedures.…”
Section: Introductionmentioning
confidence: 99%